Attitudes and practices of veterinarians in Australia to acute pain management in cats. Issue 8 (August 2022) - Rae, Louise; MacNab, Natalie; Bidner, Sarah; Davidson, Cameron; McDonagh, Phillip
Objectives: Up-to-date information on the current practices and attitudes of veterinarians in Australia to acute pain management in cats was sought in 2017–2018 in the first nationwide survey in over 20 years. Methods: An online survey was created, consisting of 54 questions in four sections, with 18 feline-specific questions. Veterinarians throughout Australia were invited to participate in the survey through advertisements in the veterinary press, electronic and regular mail, and through in-clinic visits and promotional materials. Results: A total of 614 veterinarians completed the survey, with 513 (83.6%) completing the feline-specific section. The demographics of the respondents of this survey were an accurate representation of the registered veterinarians in Australia at the time. Multiple different opioids and non-steroidal anti-inflammatory drugs (NSAIDs) were widely available in practices to manage pain, with analgesic efficacy reported as the primary factor influencing drug selection. Opioids were most commonly used in the preoperative period and NSAIDs were most commonly used postoperatively. Despite the wide availability in clinic (>99%), only 55% of respondents reported regularly using local anaesthetic techniques in cats. Pain assessment of hospitalised patients was primarily performed by veterinarians (91.1%); however, 84.7% of respondents did not routinely use a validated pain scale. Conclusions and relevance: Veterinary practitioners in Australia are adequately equipped with analgesic medication to treat pain in their patients. In the management of acute pain in cats, they frequently use a multimodal approach and practice a variety of analgesic protocols. Based on the results of this survey, potential areas for improvement in feline pain management include an increase in duration of postoperative analgesia and more routine use of validated pain scales, performed by nurses and veterinarians alike, to assess individual analgesic needs.